Alterações hemogasométricas em equinos submetidos à distensão do cólon menor - Sabes, A. F. [UNESP]; Gravena, K. [UNESP]; Herdandez-Tovar, M. C. [UNESP]; Canello, V. A. [UNESP]; Bernardi, N. S. [UNESP]; Queiroz, D. J. [UNESP]; Oliveira, J. A. [UNESP]; Lacerda-Neto, J. C. [UNESP] (FapUNIFESP (SciELO), 2017)
The objective of this study was to evaluate the blood gas analysis of venous blood of horses with experimentally induced ischemic lesions on the lower colon. Eight healthy horses were used, with ages between five and eight years, mixed breed. The animals were subjected to celiotomy and four hours of lower colonic intraluminal obstruction. The harvests were made with the blood samples immediately before induction of anesthesia (T0), when the anesthesia was stabilized (T1), 4 hours after the intraluminal obstruction (T4) and during postsurgical times were performed at intervals of 12 hours to complete 72 hours (T16, T28, T40, T52, T64 and T76). The occurrence of metabolic alkalosis on T4 with respiratory compensation by hypoventilation was noted, this alkalosis period was bland and transient, returning the normal values for the specie on T16, 12 hours after the intestinal obstruction.
Blood gas alterations in horses subjected to small colon distention
Keywords: Blood gas; Horse; Obstruction